2016
DOI: 10.21927/jnki.2014.2(1).1-8
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Positif Perubahan Berat Badan Interdialisis dengan Perubahan Tekanan Darah Pasien Post Hemodialisa

Abstract: <p>Interdialysis body weight is used to determine ultra fi ltration speed on hemodialisa patients. The overload ultra fi ltration can infl uence patients hemodynamic. According to Renal Registry Indonesia, it was 11 percent in 2012 dialysis patients experienced hypotension. This observational analytic study used cohort survey aims to analyse changing of interdialysis body weight and of blood pressure among dialysis patients in RSUD Saras Husada Purworejo. In this research, 40 respondents divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…33 The findings of previous studies in Medan also concluded that high IDWG was associated with the incidence of intradialysis complications such as the occurrence of intradialysis hypertension. 34 The high IDWG also increases the occurrence of other intradialysis complications. A study in Purwokerto showed that there was correlation between IDWG and intradialytic complications in patients with a hemodialysis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…33 The findings of previous studies in Medan also concluded that high IDWG was associated with the incidence of intradialysis complications such as the occurrence of intradialysis hypertension. 34 The high IDWG also increases the occurrence of other intradialysis complications. A study in Purwokerto showed that there was correlation between IDWG and intradialytic complications in patients with a hemodialysis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Kelebihan cairan akan menurunkan kualitas hidup pasien karena timbulnya berbagai komplikasi seperti permasalahan kardiovaskuler. Penelitian di Yogyakarta juga menunjukkan terdapat hubungan antara perubahan berat badan interdialisis dengan perubahan tekanan darah post dialisis (Widiyanto, Hadi, & Wibowo, 2014). Riset lainnya juga menunjukkan kecenderungan pasien hipervolumia mengalami hipertensi intradialisis (Inrig, 2010).…”
Section: Pendahuluanunclassified
“…Berdasarkan Data Riset Kesehatan Dasar (Riskesdas) Indonesia tahun 2013, penderita GGK di Indonesia mencapai 0,2% dari seluruh penyakit di Indonesia. Selain itu, GGK di Indonesia menempati urutan kedua setelah penyakit jantung, dengan pertumbuhan hampir 100% dalam kurun waktu 2014-2015. (Riskesdas, 2013dalam Soraya 2017.…”
Section: Pendahuluanunclassified